Oxygen uptake, acid-base balance and hormonal responses in maximal 300 - 400 m running in child, adolescent and adult athletes - Vilmi, Nikke (2013)
Vilmi, Nikke (2013). Oxygen uptake, acid-base balance and hormonal responses in maximal 300 - 400 m running in child, adolescent and adult athletes. Department of Biology of Physical Activity, University of Jyväskylä, Master's thesis, Science of Sport Coaching and Fitness Testing, 55 pp.